The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.4322/rbpv.01802004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of indirect ELISA based on recombinant protein NcSRS2 and IFAT for detection of Neospora caninum antibodies in sheep

Abstract: Neospora caninum, an Apicomplexan parasite that can causes abortion, is responsible for considerable economic and reproductive losses in livestock. The purpose of the present study was to determine whether recombinant NcSRS2 is a suitable indirect ELISA antigen for determining specific immune response to N. caninum in sheep. A total of 441 serum samples were subjected to IFAT and rNcSRS2 based-ELISA, with both tests performing similarly. The sensitivity and specificity of indirect ELISA were 98.6 and 98.3%, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 16 publications
0
7
2
Order By: Relevance
“…Regarding N. caninum, the occurrence of 23% seropositivity in sheep from this region was also higher than the majority of data reported in different regions of Brazil, ranging from 3.2% in the southern region (Vogel et al, 2006) to 15% in the northeast region (Uzeda et al, 2007), except for a higher seroprevalence of 29% in Rondônia, in the Amazon region and 31-32% in Campo Grande, in the central region of the country (Andreotti et al, 2009). Although positive association was found between seropositivity for T. gondii and the age of the animals, such association was not found for N. caninum only, as previously reported by other studies (Figliuolo et al, 2004;Romanelli et al, 2007;Spilovská et al, 2009), suggesting that vertical transmission could occur in sheep farms, similar to bovine infections.…”
Section: Discussioncontrasting
confidence: 55%
“…Regarding N. caninum, the occurrence of 23% seropositivity in sheep from this region was also higher than the majority of data reported in different regions of Brazil, ranging from 3.2% in the southern region (Vogel et al, 2006) to 15% in the northeast region (Uzeda et al, 2007), except for a higher seroprevalence of 29% in Rondônia, in the Amazon region and 31-32% in Campo Grande, in the central region of the country (Andreotti et al, 2009). Although positive association was found between seropositivity for T. gondii and the age of the animals, such association was not found for N. caninum only, as previously reported by other studies (Figliuolo et al, 2004;Romanelli et al, 2007;Spilovská et al, 2009), suggesting that vertical transmission could occur in sheep farms, similar to bovine infections.…”
Section: Discussioncontrasting
confidence: 55%
“…Among the studies conducted in Brazil with identical techniques and cut-off points, similar results were found by Faria et al (2010) in Alagoas (9.6%) and Munhóz et al (2010) in São Paulo (13.9%). However, the prevalence verified in this study was higher than the rates identified by Salaberry et al (2010) in Minas Gerais (8.1%) and Figliuolo et al (2004) in São Paulo (9.2%), and lower than the rates found by Andreotti et al (2009) in farms in the city of Campo Grande, central-western Brazil (30.8%), by Rossi et al (2011) in Minas Gerais (47.1%) and by Tembue et al (2011) in Pernambuco (64.2%). Variations by location might be related to differences in the region, climate, animal age, sample size (Dubey et al, 2011), production systems (Melo et al, 2001), or even pathogenic synergism (Melo et al, 2004).…”
Section: Resultscontrasting
confidence: 80%
“…These values were used to calculate the individual-level true seroprevalence according to Noordhuizen et al (2001). SE and SP of N. caninum ELISA were 98.6% and 98.3%, respectively (Andreotti et al, 2009). For calculating the herd-level true seroprevalence, the test SE and SP were adjusted from individual-to herdlevel using the Herdacc program (Jordan and McEwen, 1998), for a median herd size of 73 animals, herd cut-off value of one animal positive indicating a positive herd and 12-28 animals sampled per herd.…”
Section: Methodsmentioning
confidence: 99%